Two new species and a key to the dustywings of Mexico (Neuroptera, Coniopterygidae) - Sarmiento-Cordero, Mariza Araceli; Contreras-Ramos, Atilano (Zootaxa, 2019)
Two new species of Coniopterygidae are described from Mexico: Neoconis szirakii sp. n. and Coniopteryx (Scotoconiopteryx) josephus sp. n., increasing the number of recorded species of dustywings from Mexico to 43. Descriptions and illustrations are based primarily on male genitalia. A key to the known species of Coniopterygidae from Mexico is included.